Analisis Insentif Terhadap Motivasi Kerja Tim Pemasaran Dalam Sistem Pengendalian Manajemen Di Bumida Surabaya - Maulidya Roosmanningrum; Sari Andayani (CV. ITTC INDONESIA, 2026)
The incentive system plays a strategic role in shaping the work motivation of marketing teams, particularly within the context of management control that emphasizes result-based productivity. This study explores the dynamics of formal and informal incentives implemented at PT Asuransi Umum Bumi Putera Muda 1967, Surabaya Branch, and how variations in supervisory policies influence team morale and loyalty. Using a descriptive qualitative approach and semi-structured interview techniques, the findings reveal that clear, fair, and relevant incentives significantly enhance competitive spirit and work accountability. The integration of the incentive system with the management control system proves effective in fostering team synergy through results control, action control, and cultural control. However, the misalignment between workload and rewards remains a challenge in achieving overall job satisfaction. Strategic recommendations, such as digitalizing incentive reporting and diversifying forms of rewards, are essential to drive loyalty and long-term target achievement. This study also reinforces the relevance of agency theory in designing adaptive and participative control mechanisms within the financial services work environment.